The falciform ligament: anatomical study with microsurgical implications - Altafulla, Juan J.; Iwanaga, Joe; Kikuta, Shogo; Prickett, Joshua; Ishak, Basem; Uz, Aysun; Dumont, Aaron S.; Tubbs, R. Shane (Clinical neurology and neurosurgery, 2020)
Objectives - The current study aims to increase awareness of the falciform ligament and its anatomical and surgical relationships, for the benefit of the neurosurgeon. - Patinents and Methods - Twenty-four sides from twelve Caucasian cadaveric heads (all fresh-frozen) were used in this study. The length and thickness of the falciform ligament were recorded. The relationship of the falciform ligament to the optic nerve was also observed and documented. Finally, the force needed to avulse the falciform ligament was recorded. - Results - In all specimens, the ligament was identified as a continuation of the outer dural layer, forming a roof at the entrance of the optic canal. The mean medial-to-lateral length, anteroposterior length, and thickness of the falciform ligament were 7.97 mm, 2.12 mm, and 0.26 mm, respectively. The mean distance from the medial attachment of the ligament to the midline was 5.54 mm. For the undersurface of the falciform ligament, the optic nerve occupied the middle third in 50.0 %, the lateral third in 44.4 %, and the medial third in 5.6 % of sides. The mean optic nerve diameter at the entrance of the optic canal was 4.20 mm. The mean failure force was 2.47 N. - Conclusion - The anatomical measurements and relationships provided in this description of the falciform ligament serve as a tool for surgery selection and planning, as well as an aid to improving microsurgical techniques, with the final goal being better patient outcomes.